The Determinants of the Relative Importance of Small Business - White, Lawrence J. (The Review of Economics and Statistics, 1982)
SMALL businesses are prevalent in some sectors of the economy and relatively scarce in others. If we use two frequently employed definitions of small business-firms with annual sales at or below $500,000 or $5 million'-we can see the relative patterns in table 1: Agriculture, construction, wholesale and retail trade, and services are areas in which small businesses are relatively important; mining and manufacturing are areas in which they are less important. Why does small business flourish in some sectors and not in others? This question has been tackled in a qualitative fashion by a number of authors.2 But, to this author's knowledge, there have been no quantitative efforts to establish the determinants of small business prevalence. The closest approximations in the economics literature are, in effect, the inverse: the efforts to explain concentration in individual industries (e.g., efforts to explain the sizes of the four-firm or eight-firm concentration ratios across industries).3 Some of these concentration data have also been analyzed in the context of discussions about small business.4 But the concentration data provide only indirect evidence for the small business question. This paper will provide some direct cross-section evidence on the determinants of the relative importance of small business. Our sample will be limited to the manufacturing sector, largely for reasons of data availability, but the results should have general economy-wide applicability. Section II will discuss the major hypotheses to be tested. Section III will describe the data. Section IV will describe the results of the tests. And section V will provide some brief conclusions.